2022
DOI: 10.1155/2022/6547849
|View full text |Cite
|
Sign up to set email alerts
|

ICU Length of Stay and Factors Associated with Longer Stay of Major Trauma Patients with Multiple Rib Fractures: A Retrospective Observational Study

Abstract: Background. Chest injury with multiple rib fractures is the most common injury among major trauma patients in New South Wales (23%) and is associated with a high rate of mortality and morbidity. The aim of this study was to determine the intensive care unit (ICU) length of stay (LOS) among major trauma patients with multiple rib fractures and to identify factors associated with a prolonged ICU LOS. Materials and Methods. Single-centre, retrospective observational cohort study of adult patients with 3 or more t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Previous research has indicated strong correlations between a high Injury Severity Score (ISS) within the ‘very severe injury’ category and both prolonged ICU stays exceeding 7 days and increased mortality rates [ 25 , 26 , 27 , 28 , 29 ]. However, the findings for the SA group are contrary to this established correlation.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has indicated strong correlations between a high Injury Severity Score (ISS) within the ‘very severe injury’ category and both prolonged ICU stays exceeding 7 days and increased mortality rates [ 25 , 26 , 27 , 28 , 29 ]. However, the findings for the SA group are contrary to this established correlation.…”
Section: Discussionmentioning
confidence: 99%
“…[ 9 ] Injury severity scores (ISS) were obtained from a prospectively collected trauma database with a range of 1–75 and a score >15 indicating a major traumatic injury. [ 10 ]…”
Section: Methodsmentioning
confidence: 99%
“…Rib fractures are the most common injury following blunt thoracic trauma 1,2 and can lead to a range of complications, including pneumonia, 3 atelectasis, 4 and respiratory failure. These complications carry significant morbidity, often leading to extended ventilator time, 5 prolonged time in the intensive care unit (ICU) 6,7 and increased length of stay 8 . Early identification of patients at risk is essential for appropriate management and early intervention 9,10 .…”
mentioning
confidence: 99%